Dizziness and nausea vomitting induced by ropinirole therapy in an elderly patient with Parkinson’s disease : a case report - Emilia Sidharta; Hanny Cahyadi (Universitas Islam Indonesia, 2020)
Background: Ropinirole is a non-ergoline dopamine agonist drug that is widely used in a therapy for patients diagnosed with Parkinson’s disease. In long-term use, several published studies have mentioned the occurrence of side effects of ropinirole in the therapy of Parkinson’s disease, but there has been no case report on the occurrence of side effects in the form of dizziness and nausea-vomiting, especially in Indonesia. Case Presentation: This case study reported the occurrence of side effects in the form of dizziness and nausea-vomiting experienced by a 74-year-old elderly who was undergoing a treatment in a hospital in Indonesia. The patient was diagnosed with Parkinson's 8 months ago and has been given a combination therapy of levodopa-benserazide and trihexyphenidyl. During such period, no side effects occurred. The therapy was then supplemented with 2 mg ropinirole because the patient complained that his hand started shaking again. Some side effects arose after the addition of 2mg ropinirole; therefore, the side effects were thought to be associated with ropinirole. The assessment methods used were the time-series data collection followed by causality analysis using the Naranjo Scale. The analysis showed a score of 6, indicating Probable. Based on the literature review, side effects such as nausea and vomiting may occur due to the activation of dopamine D2 receptors in the Chemoreceptor Trigger Zone (CTZ) area. The CTZ area consists of several receptors, which are sensitive to the causative agent of emesis and produce information on the vomiting center that has a role in triggering the vomiting reflexes.Conclusion: Analysis using Naranjo Scale shows a score of 6 which indicates a probable association between dizziness, nausea-vomiting and ropinirole in an elderly patient with Parkinson’s Disease.Keywords: ropinirole, Parkinson, case report, elderly, side-effects